Quantitative and functional changes in platelets and fibrinogen following cardiopulmonary by-pass in children - Plebani, Margherita; Longchamp, David; Lauwers, Pauline; Di Bernardo, Stefano; Perez, Maria-Helena (Frontiers in Pediatrics, 2024)
Introduction: Cardiopulmonary bypass (CPB) causes coagulopathy, increasing the risk of postoperative bleeding and mortality. The underlying causes of post-CPB coagulopathy and the factors associated with its occurrence are not yet fully understood. This study assesses platelet and fibrinogen concentration and function following CPB in children with congenital heart diseases (CHD). Methods: We analyzed prospective data from 104 patients aged 0 to 16 years who underwent CPB surgery for CHD. Blood samples were collected before surgery and within 30 minutes of CPB completion. In addition to usual coagulation tests, functional analyses were performed using point of care systems with thromboelastometry and impedance aggregometry. Results: Platelet count, fibrinogen concentration, and platelet and fibrinogen activities significantly decreased after CPB. The duration of CPB was directly associated with a reduction in platelet count and fibrinogen level (r=-0.38, p<0.001; r=-0.21, p=0.03, respectively), but not with their measured activity. Postoperative percentages of baseline values for platelet count (58.36% [43.34 - 74.44] versus 37.44% [29.81 - 54.17], p<0.001) and fibrinogen concentration (73.68% [66.67 - 82.35] versus 65.22% [57.89 - 70.83], p<0.001) were significantly higher in patients who did not experience hypothermia during surgery. Age was inversely associated with the decrease in platelet count (r=0.63, p<0.001), TRAPTEM AUC (r=0.43, p<0.001), fibrinogen concentration (r=0.44, p<0.001) and FIBTEM MCF (r=0.57, p<0.001). Conclusion: Post-CPB coagulopathy is multifactorial and not solely attributed to hemodilution. It also involves functional changes in coagulation cascade components, which can be demonstrated by thromboelastometry and impedance aggregometry. Young children, patients requiring prolonged CPB surgery, or those experiencing hypothermia are particularly affected.